Rescue the Food: Building a Sustainable Food System for a Nourished Future - Faza, Farah; Hardiyanti, Marina; Witaningrum, Riani; Ermamilia, Aviria (Media Gizi Indonesia, 2026)
Introduction: The national food security system ensures availability and stability, yet inequitable access and food utilization contribute to malnutrition and obesity. To achieve sustainable food security and SDG 2030 goals, education and redistributing surplus food can enhance community awareness and reduce food loss and waste (FLW). Aims: To initially assess community needs and evaluate an interprofessional-based educational program on sustainable food systems and nutrition security known as "Food for Health, Food for Planet." Methods: A half-day workshop was conducted to 34 participants coming from academics, food, and health enthusiasts, nutritionist, practitioners, students, and the public. The workshop lasted for six (6) hours, consisted of pre- and post-knowledge assessment, three (3) sessions of lectures, one (1) session of talkshow, and exhibition. This event involved four (4) speakers from various backgrounds.  Result: A pre- and post-assessment survey on FLW and food sustainability showed a slight decline in scores (98.3 to 97.4, p > 0.05).  For research and education, the initiatives were conducting multi-years research, designing intensive and innovative face-to-face training, integrating food system and FLW in classroom activity, and developing a curriculum and training kit materials. Finally, the event identified: (1) follow-up research opportunities, (2) multi-helix coordination from academia/researcher, private sectors, media, and policy makers, and (3) collaborative efforts while addressing the workshop’s strength and limitations. Conclusions: This half-day workshop briefly describes the needs of community to thrive sustainable food security as well as food systems by carrying through several initiatives for reducing FLW.